2016
DOI: 10.1177/0363546516660075
|View full text |Cite
|
Sign up to set email alerts
|

Return to Sport After Primary and Revision Anterior Cruciate Ligament Reconstruction: A Prospective Comparative Study of 552 Patients From the FAST Cohort

Abstract: NCT02511158 ( ClinicalTrials.gov identifier).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
98
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(111 citation statements)
references
References 25 publications
11
98
2
Order By: Relevance
“…Post hoc analysis. Scores for each KOOS subscale from our cohort were within a previously established range of KOOS scores at 6 months following ACLR in other cohorts (31,32). After controlling for 6-month post-ACLR KOOS pain subscale scores, the significant associations observed between 6-month walking speed and 12-month interextremity mean T1q relaxation time ratio for the posterior MFC (r = À0.481, P = 0.031) and central MFC (r = À0.454,…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Post hoc analysis. Scores for each KOOS subscale from our cohort were within a previously established range of KOOS scores at 6 months following ACLR in other cohorts (31,32). After controlling for 6-month post-ACLR KOOS pain subscale scores, the significant associations observed between 6-month walking speed and 12-month interextremity mean T1q relaxation time ratio for the posterior MFC (r = À0.481, P = 0.031) and central MFC (r = À0.454,…”
Section: Resultssupporting
confidence: 65%
“…(31, 32) After controlling for 6 month post-ACLR KOOS Pain subscale scores, the significant associations observed between 6 month walking speed and 12 month inter-limb mean T1ρ relaxation time ratio for Posterior-MFC (r=−.481, P=0.031) and Central-MFC (r=−.454, P=0.05) remained significant. Similarly, the significant association observed between 12 month walking speed and 12 month inter-limb T1ρ relaxation time ratio in the Posterior-MFC (r=−.438, P=0.042) remained after controlling for 12-month post-ACLR KOOS Pain subscale scores.…”
Section: Resultsmentioning
confidence: 94%
“…Furthermore, almost two third of the patients in both groups were male. A higher amount of male patients in studies on ACL revision surgery is coherently reported across the literature [8,9,11,16,[29][30][31]. The extended analyses of the preexisting tunnels of all 103 patients included revealed a tunnel malpositioning in 90.3% at the femur and in 34% at the tibia.…”
Section: Discussionmentioning
confidence: 78%
“…The majority of the literature [7-12, 13•, 14•, [15][16][17][18][19][20][21][22] indicates a battery of tests is necessary to assess various outcome parameters and establish criterionbased clinical reasoning for RTS. This review acknowledges multiple tests that should be done aside from medical approval and clearance by the physician to verify a successful RTS such as follows: range of motion, KT1000/KT2000, Lachman's test, Pivot shift test, isotonic strength tests, isokinetic strength tests, maximum force/peak torque, angle-specific torque testing, rate of force development, hop tests, jump landing tasks (LESS), knee proprioception/kinesthesia/joint position sense testing, quality of movement tests, kinematic analysis, psychological factors/tests based on the anterior cruciate ligament-return to sport after injury (ACL-RSI) scale, PROs: anterior cruciate ligament-return to sport after injury (ACL-RSI) scale, IKDCs, KOOSs, ADL scales, Sport scales, knee self efficacy scale, Quality of Scales, ACL-RSI, Tegner Activity Scale (TAS), Lysholm Scale, and Tampa Kinesiophobia Index.…”
Section: This Article Is Part Of the Topical Collection On Acl Rehabmentioning
confidence: 99%